FENOMENA ENDORSEMENT DI INSTAGRAM STORY PADA KALANGAN SELEBGRAM - Aura Ramadhan; Cut Nadia Naswandi; Citra Maharani Herman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2020)
Instagram is the first largest social media in the world with a total of 26,9 billion active users in 2020. In Indonesia alone, several new phenomena such as endorsement and paid promotion have been carried out by celebrities famous for Instagram. This study aims to analyze the motivations behind endorsement of both the brand and the party itself. And the effect of endorsement on followers. The study was conducted on one of the celebrities with their @rachelvennya account. This research uses a qualitative method with a descriptive approach. And the data collection methods used in this research are interviews, documentation studies and literacy studies. The results in this study indicate that with the emergence of new media such as Instagram, the rise of celebrities is used as a tool to market products from online stores. Where this endorsement phenomenon arises because of the appropriate reciprocity between endorsement service users and also with endorsers. Celebrities who become opinion leaders succeed in making Instagram followers interested in what they are marketing on Instagram stories.